Collecting Taxes - Prebble, John (Victoria University of Wellington Law Review, 2002)
This article serves as a commentary for this special issue of the Victoria University of Wellington Law Review dedicated to Sir Ivor Richardson, in particular for the articles in the issue relating to the law of taxation written by Robert McLeod ("Collecting Taxes" (2002) 33 VUWLR 371) and Dr Geoffrey Harley ("Collecting Taxes" (2002) 33 VUWLR 333). The author discusses the relationship between economics and tax law and laments the fact that the discipline of "law and economics" had little to offer to the courts’ approach to fundamental principles of income tax law. The author then goes onto discuss the legislative response to the primacy of legal substance over economic substance, which typically leads to a loss of government revenue as well as recharacterising the results of the courts’ legal analysis. The author also discusses purposive approach to legislative interpretation found in the Smout decision. It is concluded that the two tax articles afford valuable insights into several characteristics of income tax law that are often obscure.